UPAYA MENINGKATKAN HASIL BELAJAR KIMIA MATERI IKATAN KIMIA DENGAN MENGGUNAKAN METODE EXAMPLE NON EXAMPLE PADA PESERTA DIDIK KELAS X MIPA 3 SMA NEGERI 72 JAKARTA - Isnaini Chomsiatun (JOEL: Journal of Educational and Language Research, 2022)
This study aims to improve Chemistry learning outcomes with the Example non Example method for Class X MIPA 3 Students at SMA Negeri 72 Jakarta in the 2019/2021 Academic Year, making Chemistry lessons a fun lesson and forming critical thinking characters so that students can solve problems in everyday life day. The problems posed in this study are: "How to Improve Chemistry Learning Outcomes in Chemical Bonds with Example Non-Example Methods for Class X MIPA 3 Students at SMA Negeri 72 Jakarta?". This type of research is Classroom Action Research (CAR) where the teacher is the executor of learning while the researcher is the observer. The research has 4 stages, namely: 1) Planning, 2) Implementation, 3) Observation, and 4) Reflection. ng The researcher acts as a subject teacher in Class X MIPA 3 SMA Negeri 72 Jakarta with senior teachers as collaborators. The results showed an increase in learning outcomes, namely in the first cycle by 80% then in the second cycle to 100%. This means an increase of 2094. Thus the use of the Example Non Example method in chemistry subjects can improve learning outcomes. This method can be implemented by Chemistry teachers because it can improve student learning outcomes and change students' thinking that Chemistry is no longer a boring and difficult subject, but a fun lesson